Environmental risk framework and research recommendations for SMS mining in the Norwegian Arctic mid-ocean ridge - Sanni, Steinar; Weaver, Phil; Flage, Roger; Mienis, Furu; Stokke, Runar; Eilertsen, Mari Heggernes; Gomiero, Alessio; Barreyre, Thibaut; Davidsen, Salva; Ribeiro, Pedro A. (Frontiers in Marine Science, 2025)
To meet future demands, mineral resources found in deposits along mid-ocean ridges have triggered the interest of the deep-sea mining industry. Comprehensive environmental management regulations are being developed by the International Seabed Authority (ISA) to control the exploitation of seabed areas beyond national jurisdiction. Norway has recently opened its seabed to mining exploration, which may potentially lead to future commercial exploitation of seafloor massive sulfides (SMS) and manganese crusts. Large uncertainties remain about the environmental consequences of such activities and improved knowledge is required to be able to describe and evaluate the associated environmental risks. An environmental risk assessment (ERA) is the process of assessing potential harm to the environment. In this paper, we apply a framework for environmental risk assessment as a mechanism to identify priority environmental knowledge, technology, and practice needed for future SMS mining operations. The ERA framework is aligned with the key elements of the draft ISA regulations and includes how risk terms and principles are understood and used by Norwegian policymakers and authorities. Regulatory draft documents, scientific literature, expert opinions, and an assessment of environmental severity, vulnerability, and value criteria have provided informative bases for the discussed research and development (R&D) recommendations. While the risk framework and associated R&D recommendations are aimed at future mining in the areas of the Arctic Mid-Ocean Ridge (AMOR) under Norwegian jurisdiction, they are also relevant to other areas of SMS exploitation and may form a useful template.